Designing bio-based plasticizers: Effect of alkyl chain length on plasticization properties of isosorbide diesters in PVC blends. (15th July 2017) - Yang, Yong; Huang, Juncheng; Zhang, Ruoyu; Zhu, Jin
Abstract: A series of bio-based plasticizers based on isosorbide, a renewable monomer derived from glucose, were successfully synthesized. The chemical structures of the synthesized isosorbide diesters with different alkyl chain length were confirmed by FTIR and 1 H NMR. The influence of varying alkyl chain length on thermal and mechanical properties of isosorbide diesters in poly(vinyl chloride) (PVC) was investigated in detail. It was found that the plasticizing efficiency of isosorbide diester decreased as the alkyl chain length increased, reflecting on the gradually increased T g and the decreased elongation at break of PVC blend. However, the longer alkyl chain length of isosorbide diester improved the thermal stability of PVC blend and simultaneously depressed its volatility from PVC. Besides, the bio-based isosorbide diesters rivaled those petro-based phthalates, and they could be potential candidates to replace phthalates in the future industry. Graphical abstract: Highlights: Isosorbide diesters with varying alkyl chain length were evaluated as bio-based alternatives to petro-based phthalates. The plasticizing efficiency of isosorbide diesters were in the order of dibutyrate > dihexanoate > dioctanoate > didecanoate. The thermostability of isosorbide diesters followed the order of dibutyrate < dihexanoate < dioctanoate < didecanoate. The isosorbide diester with longer alkyl chain length is more difficult to volatilize.